Development and validation of a stability indicating HPLC method to determine diltiazem hydrochloride in tablets and compounded capsules - Mateus Araújo Castro e Souza; Carlos Eduardo de Oliveira Pereira; Fernando Henrique Andrade Nogueira; Gerson Antônio Pianetti (Universidade de São Paulo, 2017)
ABSTRACT A stability indicating HPLC method to determine diltiazem hydrochloride (DTZ) in tablets and compounded capsules was developed and validated according to Brazilian and the International Conference on Harmonization (ICH) guidelines. The separation was carried out on a Purospher Star® C18 (150 x 4.6 mm i.d., 5 µm particle size, Merck Millipore) analytical column. The mobile phase consisted of a 0.05% (v/v) trifluoroacetic acid aqueous solution and a 0.05% trifluoroacetic acid methanolic solution (44:56, v/v). The flow rate was 1.0 mL.min-1 with a run time of 14 minutes. The detection of DTZ and degradation products (DP) was performed at 240 nm, using a diode array detector. The method proved to be linear, precise, accurate, selective, and robust, and was adequate for stability studies and routine quality control analyses of DTZ in tablets and compounded capsules.